TANTANGAN DAKWAH DIGITAL DALAM SIKAP BERAGAMA TEOLOGI INKLUSIF: PANDANGAN KOMUNITAS MUSLIM MODERAT INDONESIA DI MEDIA SOSIAL - Khofifah Sekar Ningrum (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study explores the challenges of digital da'wah based on inclusive theology within the context of the religious attitudes of Indonesia’s moderate Muslim community on social media. Amid growing polarization of religious discourse and the dominance of exclusive narratives in the digital space, moderate Muslims seek to promote a da'wah approach rooted in tolerance, pluralism, and humanistic values. Through analysis of digital content, communication strategies, and public responses, this research finds that inclusive da'wah faces significant obstacles, including social media algorithms that amplify intolerant content, pressure from conservative-radical groups, and low levels of digital religious literacy. Nevertheless, collaborative, creative, and inclusivity-driven strategies have proven to be effective alternatives in cultivating a more peaceful and adaptive religious public sphere in the digital era. These findings underscore the importance of strengthening inclusive theology as an ethical foundation for navigating the dynamics of religious life in Indonesia’s pluralistic society.